2018
DOI: 10.1063/1.5064369
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up approach to represent dynamic properties in coarse-grained molecular simulations

Abstract: Several molecular coarse-graining methods have been proposed in recent years to derive chemical- and state-point transferable force fields. While these force fields describe structural and thermodynamic properties in good agreement with fine-grained models and experiments, dynamic properties are usually overestimated. Herein, we examine if the long-time dynamic properties of molecular coarse-grained (CG) systems can be correctly represented by employing a dissipative particle dynamics (DPD) thermostat, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 56 publications
0
59
0
Order By: Relevance
“…In addition to the optimization of the dissipative forces, a major goal moving forward should be to gain a better understanding of the interplay between the chosen CG representation and the conservative and dissipative forces required for reproducing particular dynamical properties. Although some studies [36] have shown that the conservative forces have little impact on resulting dynamical properties, others [22] indicate that the conservative and dissipative forces are more strongly coupled as the complexity of the system increases, e.g., through the introduction of distinct components. The CG mapping determines the idealized free-energy surface (i.e., the many-body potential of mean force) for representing the structural and thermodynamic properties of the underlying system.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the optimization of the dissipative forces, a major goal moving forward should be to gain a better understanding of the interplay between the chosen CG representation and the conservative and dissipative forces required for reproducing particular dynamical properties. Although some studies [36] have shown that the conservative forces have little impact on resulting dynamical properties, others [22] indicate that the conservative and dissipative forces are more strongly coupled as the complexity of the system increases, e.g., through the introduction of distinct components. The CG mapping determines the idealized free-energy surface (i.e., the many-body potential of mean force) for representing the structural and thermodynamic properties of the underlying system.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…In fact, there appears to be no rigorous foundation for employing conservative forces to describe interactions between such supramolecular blobs [49].) As articulated very nicely in a recent paper by Deichmann and van der Vegt [22], these studies demonstrate success of the MZ-DPD approach in cases where there is a relatively clear time scale separation between the CG (P ) and removed (Q) degrees of freedom. Here we focus on applications with higher-resolution CG representations, where this time scale separation does not clearly exist.…”
Section: Dissipative Particle Dynamics (Dpd)mentioning
confidence: 97%
“…( 1) with (2) from Eq. ( 8) with (10), we apply a Markovian approximation [35] and replace K (s) (q, τ ) by K (s) (q, τ ) ≈ Λ (s) (q)2δ(τ ), where the singlechain mobility is the integral over the memory kernel…”
Section: Single Chain Dynamic Structure Factor and Mobility Functionmentioning
confidence: 99%
“…Extending these concepts to CG models that map polymers on CG chains with multiple sites is far from trivial [32,33,34]. One approach that has been rather successful in the case of oligomer molecules was to integrate over pair memory kernels and thereby derive dissipative particle dynamics (DPD) friction constants for monomers [35] -similar to earlier work by Hijon et al who used the Mori-Zwanzig formalism to construct DPD equations for CG particles representing whole star polymers[?]. However, it is not clear whether this approach will also work for large molecules, where internal chain motion is a significant source of memory and friction.…”
Section: Introductionmentioning
confidence: 99%
“…Time-or, equivalently, frequency-dependent friction arises whenever the dynamics of a many-particle system is described in a low-dimensional reaction-coordinate space [18][19][20][21][22][23][24] and its relevance for infrared (IR) spectra was clearly demonstrated in the past [25][26][27][28][29][30]. All friction contributions that decay faster or similarly as the vibrational period stem from adiabatic solvent degrees of freedom and account for dissipation into intra-and intermolecular degrees of freedom (including vibrational overtones) [31][32][33][34], these friction contributions dominate the vibrational energy relaxation and lead to homogeneous line broadening.…”
Section: Introductionmentioning
confidence: 99%